Synthesis of Li2Ti1.5O4 and its Selectivity to Li+ Exchange - Jiang, Jinhe (Asian Journal of Chemistry, 2012)
The ion-exchanger Li2Ti1.5O4 of spinel type was prepared by means of the solid state reaction crystallization method. Its ion-exchange properties for alkali ions such as saturation capacity of exchange and distribution coefficient were determined. Li2Ti1.5O4 was characterized by X-ray diffraction method. The acid treatment of Li2Ti1.5O4 causes Li+ extraction ratio to change from 50 to 90 %, while dissolution of Ti4+ is less than 7.5 %. This inorganic ion-exchanger (Li2Ti1.5O4) has the saturation capacity of exchange for Li+ higher than those for other alkali ions, the saturation capacity of exchange for Li+ reaches to 7.4 mmol/g, LiTiO-775(H) has a higher selectivity of ion exchange for Li+ than for other alkali ions. These results show that LiTiO-775(H) has better memory and selectivity of ion exchange and higher capacity of ion exchange for Li+. It is a kind of prospective ionic sieve for Li+.